Evaluation of Autologous Protein Solution Injection for Treatment of Superficial Digital Flexor Tendonitis in an Equine Model - Gaesser, Angela M.; Underwood, Claire; Linardi, Renata L.; Even, Kayla M.; Reef, Virginia B.; Shetye, Snehal S.; Mauck, Robert L.; King, William J.; Engiles, Julie B.; Ortved, Kyla F. (Frontiers in Veterinary Science, 2021)
Autologous protein solution (APS) has been used anecdotally for intralesional treatment of tendon and ligament injuries, however, its use in these injuries has never been studied in vivo. Our objective was to evaluate the effect of APS on tendon healing in an equine superficial digital flexor (SDF) tendonitis model. We hypothesized intralesional injection of APS would result in superior structural and biomechanical healing. SDF tendonitis was induced in both forelimbs of eight horses using collagenase injection. One forelimb was randomly assigned to receive an intralesional injection of APS, while the other was injected with saline. Ultrasonographic examinations were performed at weeks -1, 0, 2, 4, 8, and 12 following treatment. At 12 weeks, horses were euthanized and SDF samples harvested. Histologic evaluation, biomechanical testing, gene expression analysis, total glycosaminoglycan (GAG) and total DNA quantification were performed. Collagen type III (COL3A1) expression was significantly higher (p=0.028) in saline treated tendon than in normal tendon. Otherwise, there were no significant differences in gene expression. There were no significant differences in histologic or ultrasonographic scores between groups. Mean total DNA content was significantly higher (p=0.024) in saline treated tendons than normal tendons, whereas total DNA content was not significantly different between APS treated tendon and normal tendon. Elastic modulus was higher in APS treated than saline treated tendon, but the difference was not significant. Reduced expression of COL3A1 in APS treated tendon may indicate superior healing. Increased total DNA content in saline treated tendon may indicate ongoing healing processes, versus APS treated tendons which may be in the later stages of healing. Limitations include a relatively short study period and inconsistency in size and severity of induced lesions. Intralesional injection of APS resulted in some improvements in healing characteristics.